Retarding effect of dietary fibers from bamboo shoot (Phyllostachys edulis) in hyperlipidemic rats induced by a high-fat diet. Issue 10 (30th April 2021) - Li, Qi; Fang, Xiangjun; Chen, Hangjun; Han, Yanchao; Liu, Ruiling; Wu, Weijie; Gao, Haiyan
Abstract : Dietary fibers from bamboo shoot ( Phyllostachys edulis ) showed a hyperlipidemia prevention effect in high-fat diet induced rats. Abstract : The effects of the administration of bamboo shoot ( Phyllostachys edulis ) dietary fiber (BSDF) on high-fat diet (HDF) induced hyperlipidemia were studied with SD rat models. The results indicated that the body weight of rats and the mass of their adipose tissue were significantly ( P < 0.05) decreased after the combination treatment of soluble dietary fiber (SDF) and insoluble dietary fiber (IDF). The levels of total cholesterol, triglyceride, and low-density lipoprotein cholesterol were significantly ( P < 0.05) decreased by 30.20%, 53.28% and 35.63%, respectively, compared to those of the model group. The levels of serum alanine aminotransferase, aspartate aminotransferase, leptin, and insulin-like growth factor-1 of the SDF + IDF group were also significantly lower than those of the HDF model group ( P < 0.05). Additionally, the perirenal fat percentage and body fat percentage in the SDF + IDF group were reduced by 31.61% and 25.09%, respectively. IDF exhibited better hypolipidemic ability than SDF in HFD induced rats at the same dose, while SDF and IDF showed a synergistic hyperlipidemia prevention effect. The mRNA expression levels of lipid synthesis genes SREBP-1c and FAS were significantly down-regulated by SDF + IDF treatment ( P < 0.05). These results suggested that BSDF composed of IDF and SDF, with potential hypolipidemic effects, could be used in the production of health-beneficial food.